DIFFERENCE IN SERUM LIPID PROFILE VALUE IN PREGNANCY AND POSTPARTUM ON SEVERE PREECLAMPSIA - White, I Putu F.I; Wantania, John J.E; Mewengkang, Maya E. (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2019)
ABSTRACT Objective: Uncovering the connection of serum lipid profile (total cholesterol, triglyceride, HDL, LDL, VLDL) with preeclampsia in pregnancy and postpartum, and its outcome. Method: This is a cross-sectional comparative analytic study Result: From 28 preeclampsia subject were found, mean value of systole 165.36 mmHg and 105.71 diastole. Serum lipid profile in pregnancy and postpartum has a significant differences and correlated with preeclampsia, total cholesterol 234.5 mg/dl and 192.71 mg/dl, p=0.000; medium positive in pregnancy with systole r=0.461; p=0.013, weak positive with diastole r=0.380; p=0.046; postpartum with systole medium positive r=0.615; p=0.001, and weak positive with diastole r=0.317; p=0.100. LDL 140.5 mg/dl and 102.5 mg/dl, p=0.000; pregnancy and systole r=0.446; p=0,017; and postpartum were medium positive r=0.546; p=0.003. HDL 51.5 mg/dl and 43.5 mg/dl, p=0.003; not correlated with BP. Triglyceride 268.89 mg/dl and 208.96 mg/dl, p=0.000; pregnancy r=0.516; p=0.005; postpartum r= 0.515; p=0.005 has medium correlation with systole. VLDL 53.78 mg/dl and 41.79, p=0.000; pregnancy r=0.461; p=0.013 systole medium positive; r=0.380; p=0.046 diastole weak positive; postpartum r=0,615; p=0,001 systole strong positive. Conclusion: All parameter of serum lipid profile in pregnancy and postpartum has significant differences and related with severe preeclampsia. Total cholesterol, LDL, triglyceride, and VLDL correlated with BP in severe preeclampsia. Key word: endothelial dysfunction, lipid profile, preeclampsia